The Effect of Social Networking Sites to the Lifestyles of Teachers and Students in Higher Educational Institutions - Asad, Seguya; Mamun, Md Abdullah Al; Clement, Che Kum (International Journal of Basic and Applied Sciences, 2012)
With the creation of Social Networking Sites, colleges and universities across the globe have been playing catch-up with students. This new technology carries much weight as a new medium for students to build social connections and grow as members of their institutions [1]. With the aim of exploring the effect of social networking sites to the lifestyles of teachers and students in higher educational institutions, this research was conducted at four private universities in Bangladesh and one university in Uganda. A sample of one hundred teachers and one hundred students was respectively selected from four private universities in Bangladesh and one university in Uganda. Both qualitative and quantitative methods were applied during data analysis. The results indicated that social networking sites had several impacts on the lifestyle of students and teachers with the positive effects outweighing the negative effects. The findings confirmed that students can formulate group discussions so as to exchange their ideas, communicate to their teachers and appeal to their friends about assignments. Teachers share course related materials with their students, enables research work, creates student groups to collaborate on projects and communicate with their fellow teachers from other universities. So the principal conclusion was that the use of social networking sites should be incorporated into teachers’ and students’ lifestyles as its beneficial nature takes over its adverse side.